FACTORS THAT AFFECT THE PERFORMANCE OF EMPLOYEE AT PT. AGUNG AUTOMALL CABANG SUTOMO PEKANBARU - Syafrina, Nova; Manik, Sudarmin (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The purpose of this study to determine factors that affect the performance of employee at PT. Agung Automall Cabang Sutomo Pekanbaru. Samples in this study were mostly employees at PT. Agung Automall Cabang Sutomo Pekanbaru which amounted to 61 people. Sampling selected randomly using random sampling techniques (Sugiyono, 2010:93). While the variables studied in this research is the ability and motivation. Data analysis using multiple regression linear, using validity, reliability test, the classic assumption test, F test, t test R2. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on the results of research on the ability and motivation variables on performance can be seen from Table F value obtained for F (0,05) (58) = 4,01, while F count on the F test is obtained from the data processed by 55,820, meaning F count = 55,820 > 4,01 means there is he ability and motivation variables on performance at PT. Agung Automall Cabang Sutomo Pekanbaru. From the results of the t test that most affect employee performance at PT. Agung Automall Cabang Sutomo Pekanbaru is ability with t value 8,062 > 2,00172 meaning the partial motivation positive and significant impact on employee performance, while the results of the regression equation linear is Y = 14,456 + 0,894X1 - 0,041X2.Therefore means that any changes in the ability amd motivation of both positive and negative will be amended also on the performance of employees at PT. Agung Automall Cabang Sutomo Pekanbaru